2018
DOI: 10.21873/invivo.11420
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Left Ventricle Function and Subclinical Atherosclerosis in Patients with Acute Myeloid Leukemia

Abstract: Aim To assess the onset of early left ventricular (LV) systolic and diastolic function impairment and the subclinical atherosclerosis following chemotherapy in patients diagnosed with acute myeloid leukemia (AML). Materials and Methods: Thirty patients diagnosed with AML with no cardiac history, having LV ejection fraction (LVEF) >50%, were evaluated at baseline and 6 months after starting four cycles of chemotherapy. We measured LV function, global longitudinal strain and subclinical atherosclerosis markers: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The S' wave is an indicator of global systolic function, and its reduction indicates LV systolic dysfunction (20). The present results showed a reduction of S' in all the evaluated patients, supporting that the left ventricular systolic function that has suffered modifications, maybe earlier than it was expected; thus, explaining why using several methods of evaluating cardiotoxicity is recommended (21).…”
Section: Discussionsupporting
confidence: 72%
“…The S' wave is an indicator of global systolic function, and its reduction indicates LV systolic dysfunction (20). The present results showed a reduction of S' in all the evaluated patients, supporting that the left ventricular systolic function that has suffered modifications, maybe earlier than it was expected; thus, explaining why using several methods of evaluating cardiotoxicity is recommended (21).…”
Section: Discussionsupporting
confidence: 72%
“…Some reports have shown that after anthracycline administration, arterial remodelling parameters (aortic distensibility, intima-media thickness, and pulse wave velocity) are affected early through the following mechanisms: (i) anthracyclines increase the formation of reactive oxygen species and induce oxidative stress, thereby increasing arterial stiffness by causing structural changes within the vascular matrix and interfering with the endothelial regulation of vascular smooth muscle tone; (ii) vascular endothelial damage diminishes nitric oxide synthesis and promotes endothelial cell dysfunction, thereby increasing vascular stiffness; and (iii) anthracyclines promote inflammatory cytokine overexpression, which can cause endothelial injury. 7–9 Therefore, in this case, idarubicin treatment during remission induction therapy may have contributed to SAA progression.…”
Section: Discussionmentioning
confidence: 81%
“…Basic research studies have shown that anthracycline can also cause myocyte necrosis [38,39]. These diverse detrimental effects are associated with polymorphisms of anthracycline metabolism enzymes, which makes tailored safety dosing possible [12,21,40,41]. Although the mechanism of cardiotoxicity in AML has not been clarified, studies in breast cancer patients whose chemotherapy regimens contain anthracycline demonstrated that the impairment of heart cells is mediated by stress protective signaling and reactive oxygen [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports in this field mainly focused on the molecular interactions of heart toxicity, potential biomarkers, and preventive agents or were simply case reports [17][18][19][20][21][22][23]. It is also important to clarify the epidemiology of chemotherapy-related cardiacspecific death in AML patients to find some clues for basic research.…”
Section: Ivyspringmentioning
confidence: 99%